Cylindrical thin-shell wormholes and energy conditions - Simeone, Claudio Mauricio (2012)
We prove the impossibility of cylindrical thin-shell wormholes supported by matter satisfying the energy conditions everywhere, under reasonable assumptions about the asymptotic behavior of the in general differentmetrics at each side of the throat. Besides, we establish necessary conditions for the possibility of non-exotic thin-shell wormholes. © 2012 World Scientific Publishing Company.